2018
DOI: 10.3928/23258160-20180601-07
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Dexamethasone Intravitreal Implant in DME: Findings of the Prospective, Multicenter REINFORCE Study

Abstract: DEX used alone or with other DME therapy improved visual and anatomic outcomes in DME patients in clinical practice, with no new safety concerns. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:425-435.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 17 publications
6
38
0
Order By: Relevance
“…Unlike the current study, in which the interval between injections was set to 3 to 6 months, most real-life studies did not limit the interval between injections, with reported treatment intervals ranging up to 23 months. 17,24,26,28 Thus, the actual effect of the drug may be hindered by additional rescue treatments and the cumulative effect potentially lost, in turn rendering the definition of a series somewhat obsolete. Looking at the treatment effect over time within an injection series, this study demonstrated a pendular effect profile of improvement and deterioration in both visual acuity and anatomic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the current study, in which the interval between injections was set to 3 to 6 months, most real-life studies did not limit the interval between injections, with reported treatment intervals ranging up to 23 months. 17,24,26,28 Thus, the actual effect of the drug may be hindered by additional rescue treatments and the cumulative effect potentially lost, in turn rendering the definition of a series somewhat obsolete. Looking at the treatment effect over time within an injection series, this study demonstrated a pendular effect profile of improvement and deterioration in both visual acuity and anatomic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, percentage of patients who required IOP-lowering medication following the injection has been reported between 10.9% and 54%. IOP elevation is usually well-controlled with IOP-lowering medication in most of studies and the rate of patients who underwent glaucoma surgery is not reported more than 2% in any study [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Major Clinical Trials Evaluating I O P C H a N G E S A F T Ementioning
confidence: 87%
“…IOP elevation is considered a common adverse event that may occur after the administration. IOP outcomes in clinical trials of IDI are summarized in Table 1 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Different studies have reported the rates of IOP of > 25 mmHg in patients who developed IOP elevation following IDI administration are ranged from 7.1% to 58.7%.…”
Section: Major Clinical Trials Evaluating I O P C H a N G E S A F T Ementioning
confidence: 99%
See 1 more Smart Citation
“…e biodegradable implant releases dexamethasone into the vitreous over a period of ≤6 months [9]. e efficacy and safety of DEX implant have been investigated in randomized trials [3,[10][11][12], in head-to-head comparisons with anti-VEGF agents [13,14], and in a number of real-life studies [15][16][17][18][19]. In the MEAD trial, for example, DEX implant 0.7 mg or 0.35 mg provided substantial long-term improvements in visual acuity and central macular thickness (CMT) in patients with DME, with a mean of only 4 to 5 injections over 3 years [3].…”
Section: Introductionmentioning
confidence: 99%